Hardware vs Software - Haniff, Baharudin; Kam, Raslan; Mohd Azmyl, Md Yusof *; Matt, Armitage (BFM Media Sdn Bhd, 2023)
What do you get when you put an academic, who’s also a musician, a futurist and a culture vulture together in a show? A Bit of Culture, of course! Our lovely host, Kam Raslan gets the ball rolling with a topic on passions that turned out to be completely secret. What is this passion of his that’s not known to many, until now? Tune in to find out. After that, the academic-cum-musician Azmyl Yunor talks about putting subtitles on music videos, and whether that’s a good thing. Last but not least, futurist Matt Armitage shares his thoughts on the age-old physical vs digital debate and asks the team whether there are things in their lives that they still prefer to be in the physical format, over digital.